Sociology And Anthropology Of Sharia Economic Law Towards Cooperatives - Ridwan, Ahmad; Arifin, Tajul; Abdal, Abdal (Yayasan Mentari Madani, 2024)
Currently, there are many fields of science that have correlations related to views that can be displayed as a reference. Like sociology, we often know that sociology is concerned with society as a whole. But we can see from the other side such as the sociology of law that the symptoms that occur in society by referring to the rules of law that apply in a region. Sociology is often juxtaposed with anthropology. This type of research uses literature research that takes data through information by obtaining library materials, data techniques that have been obtained by reviewing and analyzing both in the form of books, journals, research results. As well as by using descriptive analysis techniques. Cooperative is a step given by fellow cooperative members to other cooperative members in the context of the welfare of their members. In addition, it is clear that the function of cooperatives is to realize community welfare in order to improve the national economy in accordance with Pancasila and the 1945 constitution. Cooperatives can be seen as a tremendous benefit for their recipients, because cooperatives can touch the lowest layers of society, help, mutual assistance taken by cooperative members indicates that the community cares about each other. When the tremendous blow experienced by cooperatives during Covid-19 made the turnover rate stagnant What is often a problem is the perception that occurs in the community related to cooperatives, often the sociology of anthropology that occurs in the community that in the article Antaranews.com, states that there are still people who are misguided in looking at cooperatives Some people consider cooperatives to be the same as loan sharking businesses that smell of usury. The sociological view of anthropology sees that something that happens in society is caused by a lack of information related to contracts, if the rights and obligations of the parties are fully fulfilled and worked out then the negative related perspective of cooperatives can be eliminated.